Improving the work evaluation and personnel management system of firefighters - LEE, Hyunseok (KDI School, 2023)
The Korean firefighting organization, which started in 1426 during the Joseon Dynasty, has made many quantitative advances over the past decade based on its high public confidence and reputation. However, it faces numerous challenges internally and complaints about the chronic personnel management and promotion system are one of the representative conflict factors. This research conducted a review of the work evaluation system and promotion system currently implemented by the firefighting organization. It focused on comparing systems operated by similar institutions such as general public officers, police, and overseas firefighting organizations, identifying complementary points, and presenting meaningful proposals. For a more objective approach, public documents and literature currently in use were analyzed and 4,529 articles posted on online forums mainly used by firefighters were statistically classified, and in-depth interviews were conducted with 21 incumbent employees to listen to opinions within the organization The policy proposal presented in this paper aims to revitalize the organization through positive motivation. By expanding objective performance indicators and ensuring evaluators' authority, a more advanced work evaluation system is established, and additional points are proposed to foster talent suitable for the future value of the organization. The final stage of the proposal is to develop into a healthy organization with appropriately distributed powers.
Thesis(Master) -- KDI School: Master of Public Management, 2023
Keywords: Fire extinction--Korea (South); Fire departments--Korea (South)